Spatio-temporal variability of glacier surface area, ELA, and AAR in the Mago river basin of Arunachal Pradesh. Issue 1 (12th January 2023) - Nunchhani, V.; Mekro, V.; Bandyopadhyay, A.; Bhadra, A.
Abstract: The spatial and temporal variations of glacier surface area, annual equilibrium line altitude (ELA), and accumulation area ratio (AAR) in Mago basin, Eastern Himalaya, are studied over 1988–2019 using Landsat data. The glacier surface area was mapped using automatic glacier extraction index (AGEI) and 49 glaciers named as G1–G49 were found in 2019. Fifteen glaciers with area greater than 1 km 2 in 2019 were selected for analysis. An automatic GIS tool comprising area altitude balance ratio (AABR), AAR, and mean glacier elevation (MGE), and combination of NIR band and Otsu threshold, were used for determining ELA. All glaciers experienced area shrinkage with a total loss of 15.22 km 2 (28.48%) at 0.49 km 2 (0.92%) per annum. G1, G9, G15, G35, G41, and G42 showed significant decreasing trend in area. Glaciers facing South-West showed highest deglaciation. For the annual ELA, all glaciers showed increasing trend and significant increasing trend was observed in G2, G15, and G40. Overall, there was an increase in ELA by 137.3 m at 4.43 m/year. The average AAR varied from 0.44 to 0.97. Average AAR of about 0.8 was observed in South, South-East, and North facing, about 0.6 in South-West and West facing, and about 0.7 in East facing glaciers. HIGHLIGHTS: The spatial and temporal variations of glacier surface area, annual equilibrium line altitude (ELA), and accumulation area ratio (AAR) in an Eastern Himalayan basin throughout for 1988–2019 were studied. The glacier dynamics of Eastern Himalayan basins, which is very different from well-studied Western Himalayan basins, have been observed and discussed. Graphical Abstract